PENDIDIKAN DAN DUNIA TEKNOLOGI INFORMATIK - Suryana, A; Mutaqin, Muhtajul; Gozali, Laili Rizki Nurilahi; Fathurrahman, Asep (PAI RAFAH, 2024)
In the world of education and information technology here is where information technology has opened the eyes of the world to a new world, a new advertise put, and a world business network without borders. Education in Indonesia leads to the involution of education 10. Efforts made by the government often set a negligible limit for passing the UN with a score of 4.25 or 5.00. Ineffectiveness is a suitable word to describe the pattern of our current learning system, because along with the times, the exchange of information is becoming faster and faster, very slowly with the development of IT and the mobility of information itself. To prevent information flooding, educative personnel are needed as direct controllers in the academic environment and parents in the home environment to jointly provide clear explanations not covered up to students. Thus, they get the right and useful information